2018
DOI: 10.1002/adem.201701041
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Ductility of Mg–Gd–Y–Zr Alloy through Extrusion and a Following Rolling

Abstract: Ductility of the Mg-8Gd-3Y-0.4Zr alloy is improved through extrusion and a following rolling performed on the as-cast alloy. Microstructure evolution, texture, and mechanical properties of the alloy are systematically investigated.The results indicate that the continuous-cluster distributed β phase particles observed in the as-cast alloy are fragmented and dissolved during the plastic deformation. Nearly random texture, improved ductility (by 60%), and strength (by 23%) are obtained. To uncover the formation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[23,24] The hot working process, especially extrusion, is often used to manufacture high-strength and high-ductile Mg alloys. [25,26] It is critical to optimize the processing parameters for achieving the desired postdeformation properties based on the deformation behavior and microstructure evolution. As is known, the constitutive model and processing map have been extensively used to study the flow behavior and optimal forming windows.…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] The hot working process, especially extrusion, is often used to manufacture high-strength and high-ductile Mg alloys. [25,26] It is critical to optimize the processing parameters for achieving the desired postdeformation properties based on the deformation behavior and microstructure evolution. As is known, the constitutive model and processing map have been extensively used to study the flow behavior and optimal forming windows.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium alloys are often associated with low strength and insufficient ductility. However, research efforts in the development of new magnesium alloys have shown that by adding rare earth elements, alloys with excellent mechanical properties can be obtained [1]. In some alloying systems-such as Mg-Y-Zn-so-called LPSO (long period stacking ordered) structures occur which contribute significantly to improving the strength and ductility of these alloys [2,3].…”
Section: Introductionmentioning
confidence: 99%